Anterior Insula Regulates Multiscale Temporal Organization of Sleep and Wake Activity - Chen, Michael C. (J Biol Rhythms, 2016)
The role of specific cortical regions in sleep-regulating circuits is unclear. The anterior insula (AI) has strong reciprocal connectivity with wake and sleep-promoting hypothalamic and brainstem regions, and we hypothesized that the AI regulates patterns of sleep and wakefulness. To test this hypothesis, we lesioned the AI in rats (n = 8) and compared sleep, wake, and activity regulation in these animals with nonlesioned controls (n = 8) with 24-h sleep recordings and chronic infrared activity monitoring. Compared to controls, animals with AI lesions had decreased wakefulness and increased rapid eye movement (REM) sleep and non-REM (NREM) sleep. AI-lesioned animals had shorter wake bouts, especially during the active dark phase. AI-lesioned animals also had more transitions from NREM to REM sleep, especially during the inactive light phase. Chronic infrared monitoring revealed that AI-lesioned animals also had a disturbed temporal organization of locomotor activity at multiple time scales with more random activity fluctuations from 4 to 12 h despite intact circadian rhythms. These results suggest that the AI regulates sleep and activity and contributes to the regulation of sleep and motor behavior rhythmicity across multiple time scales. Dysfunction of the AI may underlie changes in sleep-wake patterns in neurological diseases.